Assessing the Effect of Apremilast on Serum Leptin levels in Obese Patients with Psoriasis - Saad, Haitham Mohammed; Noaimi, Adil A.; Mahmood, Halla G. (AL-Kindy College Medical Journal, 2024)
Background: Psoriasis is a common inflammatory condition worldwide, with an average prevalence ranging from 2% to 3%. However, the incidence of psoriasis varies among different ethnic groups and regions. Elevated leptin levels have been associated with increased cellular proliferation, including T-cells. Additionally, high leptin levels may stimulate the synthesis of proinflammatory cytokines such as ILـ6 and TNFـα. Objectives: To evaluate the effect of Apremilast on Leptin in obese psoriatic patients. Subjects and Methods: Thirty patients with psoriasis were included in This prospective cohort study to measure the levels of serum Leptin by using the ELISA technique, before and after receiving Apremilast. Result: The present work found the concentration of Leptin before receiving Apremilast was 2.365 ng/ml, and after six months from baseline, it was reduced to 1.933 ng/ml, which was statistically significant (P<0.05). Conclusion: This prospective cohort study provides evidence that Apremilast can decrease elevated Leptin levels in individuals diagnosed with psoriasis. The study observed a 0.42 ng/ml reduction in Leptin levels after 6 months of Apremilast treatment.